2007
DOI: 10.1109/jstqe.2007.902088
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Silicon Single-Photon Avalanche Diodes

Abstract: Silicon single-photon avalanche diodes (SPADs) are nowadays a solid-state alternative to photomultiplier tubes (PMTs) in single-photon counting (SPC) and time-correlated single-photon counting (TCSPC) over the visible spectral range up to 1-mum wavelength. SPADs implemented in planar technology compatible with CMOS circuits offer typical advantages of microelectronic devices (small size, ruggedness, low voltage, low power, etc.). Furthermore, they have inherently higher photon detection efficiency, since they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
251
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 273 publications
(257 citation statements)
references
References 45 publications
5
251
1
Order By: Relevance
“…Especially when they are absorbed outside the active layer of the device, these trapped charges can have a lifetime much longer than the deadtime, and can therefore be released after the operating voltage has been restored, causing an avalanche, which is indistinguishable from one caused by an incident photon. These afterpulses are most likely to occur at the end of the deadtime but can spread over several ms, with probability decreasing further from the original hit [26]. The decay in afterpulse probability in the LDM has been found experimentally to be best fitted by multiple exponentials, with the main components having time constants of 25 and 45 ns.…”
Section: A Jeff Et Al / Nuclear Instruments and Methods In Physics mentioning
confidence: 99%
“…Especially when they are absorbed outside the active layer of the device, these trapped charges can have a lifetime much longer than the deadtime, and can therefore be released after the operating voltage has been restored, causing an avalanche, which is indistinguishable from one caused by an incident photon. These afterpulses are most likely to occur at the end of the deadtime but can spread over several ms, with probability decreasing further from the original hit [26]. The decay in afterpulse probability in the LDM has been found experimentally to be best fitted by multiple exponentials, with the main components having time constants of 25 and 45 ns.…”
Section: A Jeff Et Al / Nuclear Instruments and Methods In Physics mentioning
confidence: 99%
“…Our N00N-state source produces high-fidelity, high-N N00N PRL 112, 223602 (2014) P H Y S I C A L R E V I E W L E T T E R S week ending 6 JUNE 2014 states [15,16,20], and we have shown that the N00N state OCM signal displays N-fold superresolution, and a visibility that is nearly independent of N. Thus, our implementation is naturally applicable to higher photon numbers. This could be achieved using several exciting new technologies which are continually advancing, such as high-efficiency single-photon detectors [23,24], high-fillfactor single-photon detector arrays [25], and brighter down-conversion sources with high coupling efficiency [21,22]. Our experiment demonstrates a practical implementation to overcome the problem of efficiently detecting N-photon states-a fundamental challenge to practical quantum metrology-and could open the door for Heisenberg-limited phase detection and quantum imaging.…”
Section: Prl 112 223602 (2014) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 94%
“…One issue with such planar bulk Si devices is the long carrier-diffusion length between photogenerated carriers in the neutral region and the junction region where impact ionisation occurs. Also, the guard ring diffusion poses a number of challenges, including increasing the process thermal budget, and reducing the SPDE due to nonuniform breakdown voltage across the active area [39].…”
Section: Bulk Si Apdsmentioning
confidence: 99%